Quantitative modelling of momentum in tennis based on factor analysis - Ge, Yiwei (Transactions on Computer Science and Intelligent Systems Research, 2024)
Tennis, with its playful and elegant nature, has perennially captivated individuals of all ages. Beyond being a mere game, it represents a clash of momentum. In modern sports, the term "momentum" is used to describe a player’s drive and momentum during a game. In the tennis match, it can affect the player’s rhythm of the match and the result, is the key factor to determine the result of the match. But the quantification of momentum has no definitive reference in sport. This study attempts to propose a model that can be used to quantify the momentum of tennis players based on factor analysis. In this paper, data from the men’s singles match at Wimbledon was first taken and subjected to missing and outlier detection and processing to ensure the reliability of this data. Secondly, the paper selected all the indicators that may be related to a player’s momentum for factor analysis. In this paper, the proportion of variance contribution is used as the weight of each factor to calculate the composite score as the quantitative value of momentum. The analysis and modelling process in this paper could provide new insights into the understanding and development of the sport of tennis, offering a perspective and direction to quantization. The results of the factor analysis may provide valuable perceptions for coaches and athletes to help them better understand the game situation and develop strategies for future games.